I still have a right from an ancestor of that color: struggles of the Brazilian quilombola population - Iris Pontes Soares (Revista Katálysis, 2018)
This article aims to approximate original and contemporary quilombos, trying to understand their organization and struggles agenda. Through Marxist authors recognized in the analysis of the Brazilian historical-social development such as Caio Prado Júnior (1907-1990), Jacob Gorender (1923-2013) and Clóvis Moura (1925-2003), the intention of this article is to discuss the meaning of slavery and how the quilombos organize themselves as a predominant collective form of resistance. The conclusion presents the level of racism present in Brazilian society, which operates to hide the instruments of struggle of the black people and how this had impacted today’s Brazilian working class. Bibliographical reviews were carried out to systematize the knowledge of the authors on the subject.